Rabab in Southeast Asia - Amod, Kason (Academic and Research Journal of Liberal Arts (Online), 2022)
The study of Rabab in Southeast Asia aimed to study the background and spreading of Rabab. Rabab was a type of musical instrument widely performed throughout Western Asia, Central Asia, South Asia, and Southeast Asia. Rabab was characterized by a wide variety. It might have originated in Afghanistan (Kasnawiya Empire centered on Ghazni where is located in present-day Afghanistan) that appears in northwestern India and it was accepted around the mid-18th century. Rabab has arrived in Hindustani music as a Sarod. In Afghanistan, rabab was the dominant instrument in the region as well as Pakistan and Kashmir. In Southeast Asia, there was evidence that the lute is similar to the Indian Rabab originated in a near era. That is, during the Moriya and Gupta dynasties, there was a period of movement in politics, administration, trade, and religion, thus causing the spreading of art and culture found in Thailand, Vietnam and Indonesia. There was evidence of a stucco sculpture depicting musicians playing the lutes in the central region at the ancient city of Khu Bua, Ratchaburi, in Thailand, at the Cham Museum in Vietnam and at the stupa of Borobudur Temple in Indonesia.